Authentication and Potential Analysis of Landrace Rice From Solok Region Sumatera Barat - Rahmatullah, Yudi Agustira; Syamsuardi, Syamsuardi; Maideliza, Tesri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Limited understanding of rice cultivar biodiversity information in Solok Regency makes it difficult for people to determine which local rice originates from the area. This research aims to reveal the diversity and relationships of local rice, find specific morphological characters and their contribution value in providing diversity and find local rice candidates for plant breeding through analysis of potential superior characters. The method used is a field survey method with Principle Component Analysis (PCA) analysis to describe the contribution of a character in providing diversity and Cluster analysis to reveal the relationship between local rice cultivars. The 18 rice cultivars found included 11 local cultivars, 7 superior local cultivars. 3 of them from Solok Regency; Cisokan, Caredek, Siarang and the rest were released from various West Sumatra Agricultural Services. Based on the results of Cluster analysis and Principle Component Analysis, a dendogram was formed with 3 main clusters. Then we get morphological characters that have a contribution value with an eigen value> 0.3, including characters; plant height, leaf length, leaf width, ligule length, lower stem node diameter, flag leaf angle, leaf color, midrib color, flag leaf color, and center of panicle exit. This research also provides prospective local rice cultivars that have the opportunity to become superior local cultivars, such as; Padi Cinta, Situjuah, Sungkai and Talang Solok.